Informações, percepções e concepções sobre promoção da saúde apresentadas por estudantes de enfermagem de uma faculdade privada de Uberlândia - MG - Silva, Beatriz Regina da (2009)
Several studies have been showing that professionals of the most different fields of health are not fully prepared for the implementation of actions of Health Promotion, due to the valorization of post graduations, or even of the actions considered of high complexity, in the health professional development. According to this, we intended to investigate the conceptions and perceptions regarding the Health Promotion and its influence on the actions of health, generally on nursing students of a private institute of teaching, located in Uberlândia city, Minas Gerais. For the data collection of the 37 students, which all of them accepted to take part in the research, it was used an anonymous and voluntary questionnaire. It was also used the descriptive statistics for analysis of the data achieved with multiple choice questions and the analysis of the thematic content for the data obtained with the dissertative questions. The analysis of the data showed that: 1) the context of performance of the students' larger interest is PSF; 2) the main reasons associated to the students' largest interest for PSF are: the opportunity of acting in the prevention and promotion of the health and the opportunity of keeping in contact with the population, what makes possible to know the needs of the community, the attendance and evaluation of the developed actions; 3) in the students' perception, the context of UBS is the one that less draws the nurses attention and reasons such as: smaller work journeys, lower stress level, less bureaucracy and weaker demands from the patients, together with better wages determine the nurse's interest in choosing PSF; 4) in spite of the teacher is the main source of information for the students, 56,8% of them consider themselves more or less up to dated on subjects related to public health; 5) despite the health concept of OMS is considered outdated, it still predominates among the students; 6) the students had difficulties to recognize the differences between the strategies of health promotion and the traditional preventive practices; 7) the educational activities with the objective of preventing diseases and the actions that look for the improvement of life quality were outstanding as actions the nurse can execute in different contexts; 8) the students still think education in health according to the traditional preventive model which emphasizes the importance of passing information, in order to have the prevention of diseases and this model associates health to the adoption of healthy life habits; 9) the students point out lectures as activities when developed in the community that underline the importance of the education in health; 10) the students do not know the expression empowerment and 62,1% of them didn't know what principles of the acts of public health were contemplated in the actions developed during the traineeship of collective health. The data reinforce the need of discussions, reflections and a revision of the planning of the disciplines of the area of public health and the adopted educational practices, which should promote the relation of the disciplines with the other contents of the curriculum and the integration theory-practice, conditions which collaborate to the development of the competences and necessary abilities for performance in the area of the public health.